Executive summary: Local responses to migrants with precarious status: a comparative report on frames, strategies and evolving practices in Europe - Kirchoff, M; Homberger, A; Bastick, Z; Ataç, I; Güntner, S; Spencer, S; Mallet-Garcia, M (COMPAS, 2022)
This is the executive summary of a report¹ in which we compare the findings and analysis from research on access to services for migrants with a precarious status in three European cities: Cardiff, Frankfurt am Main and Vienna. It is the concluding report of an 18-month study, Local Responses to Precarious Migrants: Frames, Strategies and Evolving Practices in Europe (LoReMi), carried out in 2021-2022. The aims of the project were to investigate the ways in which local authorities provide access to basic social services to residents whose immigration or residence status is precarious and, in that context, to explore their cooperation with public and civil society organisations. It included a particular focus on issues relating to women. Previous research has established that, for local authorities in Europe, the exclusion of a section of local residents from public services can pose challenges in relation to achieving their policy goals, such as public health and crime prevention, and reducing street homelessness and domestic violence. Some local authorities have responded with initiatives designed to ensure that basic service needs are met, whether by municipal services directly or through partnering with a non-governmental organisation (NGO). The LoReMi project set out to consider the ways in which each local authority frames its approaches towards precarious migrants and to examine the actual policies and practices in place in relation to key services such as health, education, accommodation and legal advice.